The potential utility of carotenoid‐based coloration as a biomonitor of environmental change. (27th July 2020) - Peneaux, Chloe; Hansbro, Philip M.; Griffin, Andrea S.
Abstract : In the past 30 years, carotenoid‐based animal signals have been an intense focus of research because they can potentially broadcast an honest reflection of individual reproductive potential. Our understanding of the underpinning physiological functions of carotenoid compounds is still emerging, however. Here, we argue that wildlife researchers and managers interested in assessing the impact of environmental quality on animal populations should be taking advantage of the signalling function of carotenoid‐based morphological traits. Using birds as a model taxonomic group, we build our argument by first reviewing the strong evidence that the expression of avian carotenoid displays provides an integrated measure of a multitude of diet‐ and health‐related parameters. We then present evidence that human‐induced rapid environmental change (HIREC) impacts the expression of carotenoid signals across different critical periods of a bird's lifetime. Finally, we argue that variation in signal expression across individuals, populations and species could be quantified relatively easily at a global scale by incorporating such measurements into widespread bird ringing activities. Monitoring the expression of carotenoid‐based coloration could help to identify how the environmental factors linked to HIREC can affect avian populations and allow for potentially detrimental effects on biodiversity to be detected prior to demographic change.